Reflections on Vitale’s & Hew Len’s book “Zero Limits” (2007): Holistic Psychosomatic and Spiritual Implications - Dejan Raković (International Journal of Complementary Medicine, 2025)
The paper considers holistic psychosomatic and spiritual implications of our extended quantum-holographic theoretical framework in the context of Ho'oponopono remarkable reprogramming of the life situations by contextual repenting and forgiving ourselves. This suggests the full importance of holistic education and behavior, demonstrating the necessity of reorientation towards holistic subtle actions for global solutions of the world risk society.
Keywords: Quantum-Holographic